Seismic Behavior of Composite Shear Walls with Encased Vertical Steel Sections - علي طوالو (Latakia University Journal -Engineering Sciences Series, 2022)
The concept of steel-concrete composite shear wall is introduced due to the benefits achieved by integrating both the materials. These are structural walls, where steel profiles are encased at the boundary elements. Due to their higher lateral strength and stiffness, they offer a good alternative to improve earthquake resistance over conventional reinforced concrete shear walls in medium and high-rise buildings. Shear walls generally have rectangular cross section with the high concentration of vertical reinforcement at the boundary elements. The use of conventional reinforced concrete shear wall in multistoried buildings is sometimes limited because of the high concentration of reinforcement provided at the boundary element. Composite steel-concrete shear walls with encased vertical steel sections provide good alternative. Through this research, an analytical study was presented for the possibility of replacing the vertical reinforcement of a concrete shear wall using two steel sections according to the specifications of the European code. The Lateral load-displacement values belonging to each wall, maximum load, deformation and stiffness capacity were evaluated. Comparative study indicates that presence of vertical steel sections significantly increases base shear, stiffness, and ductility.